2004
DOI: 10.1143/jjap.43.5373
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MgO-Doping on Electrical Properties and Microstructure of BaTiO3

Abstract: Degradation behaviors of Mg-doped BaTiO3 have been studied in terms of oxygen vacancy concentration and microstructural development. Mg-doped BaTiO3 powders were precisely synthesized by the Pechini method. As MgO content was increased to 1.0 mol%, Curie points moved to lower temperatures and dielectric constants decreased. The specimens doped with MgO showed higher leakage currents under the continuously applied dc field at a high temperature (100°C) during the aging process, compared with the undoped BaTiO3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
41
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 29 publications
7
41
0
Order By: Relevance
“…The maximum TSDC peak of Ba(Ti 0.99 Mn 0.01 )O 3−δ shifts to lower temperatures (<125 • C) compared with Ba(Ti 0.995 Mn 0.005 )O 3−δ , and the TSDC increases above the temperature (>125 • C) at which the maximum peak occurs. This result is compatible with the previous report that charged oxygen vacancies, in combination with acceptors, locally deform the perovskite unit cells, leading to the local reduction of the tetragonality and the decrease in the Curie temperature [13,43]. Fig.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The maximum TSDC peak of Ba(Ti 0.99 Mn 0.01 )O 3−δ shifts to lower temperatures (<125 • C) compared with Ba(Ti 0.995 Mn 0.005 )O 3−δ , and the TSDC increases above the temperature (>125 • C) at which the maximum peak occurs. This result is compatible with the previous report that charged oxygen vacancies, in combination with acceptors, locally deform the perovskite unit cells, leading to the local reduction of the tetragonality and the decrease in the Curie temperature [13,43]. Fig.…”
Section: Resultssupporting
confidence: 93%
“…(1). The equilibrium electrical conductivity indicated that oxygen vacancies are formed to compensate negatively charged Mg ions on Ti sites and the oxygen vacancy concentration of Ba(Ti 0.995 Mg 0.005 )O 2.995 is estimated to be ∼50 times greater than that of un-doped BaTiO 3 according to the relationship proposed by Smyth [13,42]. Such a large amount of oxygen vacancy formation leads to the severe electrical degradation as shown in Fig.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…This is similar to the previous study of MgO doped BaTiO 3 . 25 Excess MgO is assumed to exist in the grain boundary region and suppresses the grain growth, resulting in poor densification. Fig.…”
Section: Resultsmentioning
confidence: 99%